An anthropometry study in polycystic ovary syndrome patients - Prajapati, Pooja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Polycystic ovary syndrome (PCOS) a symptom complex, which is also known as hyperandrogenism anovulation, was first proposed by Stein and Leventhal in 1935. Methods: This observational cross-sectional study was conducted in the obstetrics and gynaecology department of SPS Hospital, Ludhiana, Punjab and included 60 women with PCOS and 30 non PCOS women of age group 18-40 who met the inclusion criteria. Results: The Mean BMI of study population was 26.39±4.17 in group A (PCOS) and 26.37±3.79 in group B (non PCOS). The calculated mean waist hip ratio of subjects was 0.73±0.08 in both groups. The mean waist height ratio of study population was 0.48±0.05 in group A and 0.49±0.04 in group B. Conclusions: Anthropometric parameters are recommended as a screening tool in women with PCOS so as to improve endocrinological and metabolic disturbances not only to treat PCOS but also to reduce long term health risks. An early treatment for obesity should be a priority to prevent cardiometabolic complications in future.